Innovation as a business driver: the Hommie case - Juliao-Esparragoza, David; Macias, Adriana; Vega-Jurado, Jaider (Estudios de Administración, 2020)
In December 2018, Alonso Macías, Manager at Mayordomia, was looking for somewhere quiet to evaluate his company’s possibilities after foreseeing a projected closing with COP 14 billion less in sales than in 2016. He needed answers to all possible questions before attending a board meeting that was looking critical for him. He wondered if it was time to diversify his business, and if the conditions of the economy and his company’s power to respond, while occupying the largest share of the market at that time, would be negatively affected. The opportunity to diversify had always been there, but previous efforts had not gone well. Entering new markets with different proposals still generated certain suspicions for him that he didn’t express when telling his team that there could be no doubt about the need to exploit the company’s infrastructure in sectors adjacent to the business and institutional cleaning and maintenance service - sectors that had already been considered and included in the 2016-2019 strategic plan since 2013. “It looks like a risky option, but Adriana and her team seem to have a clearer idea of how to bring our know-how to all the different homes and cover the B2C segment,” pondered Alonso. Although he was willing to listen to the new proposals of the team led by his daughter, between positivism, uncertainty and resistance to change, he wondered if the conditions were favorable for these innovations, and if it would be possible to successfully achieve a victory early to break with the business schemes and systems that had been a part of Mayordomia for almost 30 years. Although the president of Mayordomia has been characterized as a tenacious and courageous person, this time, at 57 years of age, he sometimes feels that uncertainty overwhelms him.